The top hat procedure does not impact the management of women treated by LEEP in cervical cancer screening - Juliana Yoko Yoneda; Aline Evangelista Santiago; Julio Cesar Teixeira; Helymar Costa Machado; Sophie Derchain; Milena Yonamine; Diama Bhadra Vale (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To describe Top-hat results and their association with margin status and disease relapse in a referral facility in Brazil. Methods: A retrospective study of 440 women submitted to LEEP to treat HSIL, in which 80 cases were complemented immediately by the top hat procedure (Top-hat Group - TH). TH Group was compared to women not submitted to Top-hat (NTH). The sample by convenience included all women that underwent LEEP from January 2017 to July 2020. The main outcome was the histological result. Other variables were margins, age, transformation zone (TZ), depth, and relapse. The analysis used the Chi-square test and logistic regression. Results: The TH Group was predominantly 40 and older (NTH 23.1% vs. TH 65.0%, p<0.001). No difference was found in having CIN2/CIN3 as the final diagnosis (NTH 17.0% vs. TH 21.3%, p=0.362), or in the prevalence of relapse (NTH 12.0% vs. TH 9.0%, p=0.482). Of the 80 patients submitted to top hat, the histological result was CIN2/CIN3 in eight. A negative top hat result was related to a negative endocervical margin of 83.3%. A CIN2/CIN3 Top-hat result was related to CIN2/CIN3 margin in 62.5% (p=0.009). The chance of obtaining a top hat negative result was 22.4 times higher (2.4-211.0) when the endocervical margin was negative and 14.5 times higher (1.5-140.7) when the ectocervical margin was negative. Conclusion: The top hat procedure did not alter the final diagnosis of LEEP. No impact on relapse was observed. The procedure should be avoided in women of reproductive age.